Heuristic perspective of marxist sociology: to the 200th anniversary of Karl Marx birthday - Shavel, Sergei A. (Journal of the Belarusian State University. Sociology, 2019)
The heuristic perspectives of Marxist sociology are analyzed. The essence of the binary opposition of assessments of attitudes toward Marxist sociology is revealed. The role of «analytical Marxism» in modern sociological research and the formation of worldview attitudes of different social groups is shown. There are reviews of well-known world sociologists such as E. Durkheim, M. Weber, N. Smelzer, T. Parsons and others. They are about the contribution of Marx to sociological knowledge. The expediency of Marx’s intuitions rethinking and the reformulation of the conceptual apparatus taking into account the current trends in the development of society is substantiated.
Keywords: Marxist sociology; post-economic society; social justice; analytical marxism; alienation; exploitation; binary opposition; solidarity; identification; collective